2021
DOI: 10.3390/horticulturae7060151
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome and Metagenome Analysis Reveals Huanglongbing Affects the Abundance of Citrus Rhizosphere Bacteria Associated with Resistance and Energy Metabolism

Abstract: The plant rhizosphere microbiome is known to play a vital role in plant health by competing with pathogens or inducing plant resistance. This study aims to investigate rhizosphere microorganisms responsive to a devastating citrus disease caused by ‘Candidatus Liberibacter asiaticus’ (CLas) infection, by using 16S rRNA sequencing and metagenome technologies. The results show that 30 rhizosphere and 14 root bacterial genera were significantly affected by CLas infection, including 9 plant resistance-associated ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Some bacterial genera like Bacillus, Methylobacterium, Halomonas , etc. were observed abundantly in citrus leaves and fruits following the infection with canker and melanosis diseases ( Li et al, 2021 ).…”
Section: Microbiome In Citrus Plant Healthmentioning
confidence: 99%
See 2 more Smart Citations
“…Some bacterial genera like Bacillus, Methylobacterium, Halomonas , etc. were observed abundantly in citrus leaves and fruits following the infection with canker and melanosis diseases ( Li et al, 2021 ).…”
Section: Microbiome In Citrus Plant Healthmentioning
confidence: 99%
“…Application of 16SrRNA sequencing and metagenomics provided a comprehensive analysis of the citrus microbiome and its response during C Las infection ( Li et al, 2021 ). A total of 30 rhizosphere and 14 root bacterial genera were affected by C Las infection, of which 9 were plant resistance-associated bacterial genera ( Chryseobacterium , Amycolatopsis , Sphingopyxis , Duganella , Flavobacterium , Ralstonia , Streptacidiphilus , and Stenotrophomonas ) loaded in C Las-infected roots, while Rhizobium population depleted.…”
Section: Citrus Microbiome and Incurring Huanglongbing: A Case Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In this survey, we confirmed that ~10% of the trees subjected to the survey remained disease-free during the entire two-year-long survey conducted by qPCR using DNA fractions prepared from leaves and fibrous roots. It has been shown that HLB compromised the recruitment and/or the composition of certain microbes in the citrus root system [ 12 , 42 ], and an attempt has been made to use bacteria with antibacterial activity isolated from the rhizosphere of the escape trees as a tool to mitigate the damage caused by HLB [ 10 ]. These data prompted us to investigate and compare the microbe population associated with the fibrous root system of trees with different HLB disease histories to investigate the potential involvement of rhizosphere microbe(s) for the tolerance against HLB as seen in the escape trees.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, if peptides are selective against the pathogen, their application can restore the microbiome that can benefit plant growth. HLB is known to have significant impacts on both the structure and functions of plant‐associated microbiome (Hu et al, 2022; Li et al, 2021; Liu et al, 2023; Trivedi et al, 2016). The HLB‐mediated changes in the plant‐associated microbiome is postulated to have a detrimental influence in overall citrus health (Trivedi et al, 2012).…”
Section: Introductionmentioning
confidence: 99%